2020
DOI: 10.1186/s13063-020-04822-0
|View full text |Cite|
|
Sign up to set email alerts
|

BCG revaccination of health workers in Brazil to improve innate immune responses against COVID-19: A structured summary of a study protocol for a randomised controlled trial

Abstract: Objectives The BCG vaccine, widely used in Brazil in new-borns, induces adjuvant protection for several diseases, including childhood virus infections. BCG activates monocytes and innate memory NK cells which are crucial for the antiviral immune response. Therefore, strategies to prevent COVID-19 in health workers (HW) should be carried out to prevent them becoming unwell so that they can continue to work during the pandemic. The hypothesis is that BCG will improve the innate immune response and prevent sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…130 It has been proposed that BCG may also offer protection against infection with SARS-CoV-2 and reduce severity of COVID-19 disease, 131 with some studies suggesting an association between universal BCG vaccination and reduced COVID-19 mortality, 132 while others did not. 133 Several randomized trials in healthcare workers 134 and elderly patients that are underway or pending final analysis will provide final proof for a protective effect of BCG against COVID-19.…”
Section: Mtb Infection In the Initial Stage Of Infection Inhaled Aerosolizedmentioning
confidence: 99%
“…130 It has been proposed that BCG may also offer protection against infection with SARS-CoV-2 and reduce severity of COVID-19 disease, 131 with some studies suggesting an association between universal BCG vaccination and reduced COVID-19 mortality, 132 while others did not. 133 Several randomized trials in healthcare workers 134 and elderly patients that are underway or pending final analysis will provide final proof for a protective effect of BCG against COVID-19.…”
Section: Mtb Infection In the Initial Stage Of Infection Inhaled Aerosolizedmentioning
confidence: 99%
“…Another large trial recruiting 800 participants has started in Brazil, with recruitment being completed by March 2021. The follow-up is for six months; the results will likely be available by the end of this year [89] . A recent study among a cohort of health care workers concluded that a history of BCG vaccination has been associated with a decrease in anti-SARS-CoV-2 IgG seroprevalence and a decrease in the number of participants self-reported with COVID-19-related clinical symptoms in this cohort [90] .…”
Section: Resultsmentioning
confidence: 99%
“…From a bottom-up perspective, animal models have shown that immunization with specific substances, such as myelin-related peptides ( Lewitus et al, 2008 ), and certain mycobacterial strains ( Reber et al, 2016 ; Loupy et al, 2021 ) can attenuate stress-induced anxiety and promote resilience via alterations in immune functioning, such as inhibition of stress-related increases in IL-6. The latter finding is of particular significance in the context of the COVID-19 pandemic, as it has been noted that immunization against Mycobacterium tuberculosis exerts a potential protective effect against COVID-19 mortality ( Li, 2021 ) and trials of BCG immunization in healthcare workers for this purpose are in progress ( Junqueira-Kipnis et al, 2020 ; Madsen et al, 2020 ). Stress-induced alterations in immune function are also under epigenetic control and may be amenable to modulation in this manner, as discussed in the next section.…”
Section: Key Research Areas In the Neurobiology Of Resilience And Thementioning
confidence: 99%